Implementasi Manajemen Risiko Keamanan Bersumber UUD 1945 dan NKRI Pada Tahap Eksplorasi Minyak dan Gas Di PT Chevron - Ridwan Zaidaan; Edy Soesanto; Mochamad Raka Putra Basarah (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
Oil and gas exploration is the process of searching, evaluating, and identifying locations beneath the Earth's surface that have the potential to contain oil and natural gas. In Indonesia, the exploration of oil and gas is regulated by Law Number 22 of 2001 concerning Oil and Natural Gas, which "regulates the management of oil and natural gas, including exploration, production, and management of oil and natural gas resources in Indonesia." Indonesia has many companies involved in oil and gas exploration and production, one of which is PT Chevron. The implementation of Security Risk Management based on the 1945 Constitution in the Oil and Gas Exploration Phase at PT Chevron is a strategic step in ensuring operational safety and security in accordance with the principles of the Indonesian constitution. The 1945 Constitution emphasizes the importance of natural resources for national interests. Chevron, as an oil company operating in Indonesia, must comply with regulations and make maximum contributions to the development of the economy and welfare of local communities. Chevron is committed to improving the welfare of local communities through programs for economic development, health, education, and infrastructure. The involvement of the community in the decision-making process is also a key focus for this company.